Social Inclusion: Policies and Practices in Nepal - Gurung, Om (Occasional Papers in Sociology and Anthropology, 2010)
Social inclusion is one of the most vibrant issues raised strongly by indigenous peoples, women, Madhesi, Dalits and other marginalized communities in Nepal. At present, this issue has been a political agenda among political leaders, a subject of academic discourse among intellectuals and a field of development priority among development practitioners. Given the fact that the present state is exclusionary, non-participatory and non-representative and discriminates against indigenous peoples, women, Madhesis, Dalits and other marginalized communities on the basis of caste, ethnicity, language, religion, sex, class and geographical territory, these marginalized peoples and communities are demanding for a inclusive state through its restructuring along the line of federalism on the basis of national regional autonomy. For this purpose the election of constituent assembly has served as a legitimate and democratic process in present day Nepal. DOI: 10.3126/opsa.v11i0.3027 Occasional Papers in Sociology and Anthropology Vol.11 2009 1-15